2021
DOI: 10.3758/s13428-021-01641-2
|View full text |Cite|
|
Sign up to set email alerts
|

Can musical ability be tested online?

Abstract: We sought to determine whether an objective test of musical ability could be successfully administered online. A sample of 754 participants was tested with an online version of the Musical Ear Test (MET), which had Melody and Rhythm subtests. Both subtests had 52 trials, each of which required participants to determine whether standard and comparison auditory sequences were identical. The testing session also included the Goldsmiths Musical Sophistication Index (Gold-MSI), a test of general cognitive ability, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 74 publications
(136 reference statements)
5
41
0
1
Order By: Relevance
“…Otherwise, ad hoc translations were created by native speakers who were also fluent in English. Correia, et al (2021) documented that the online versions and translations of all tests used in the present study had good reliability and validity, matching that of in-person testing conducted in English (Swaminathan et al, 2021), and that performance did not vary as a function of testing language.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Otherwise, ad hoc translations were created by native speakers who were also fluent in English. Correia, et al (2021) documented that the online versions and translations of all tests used in the present study had good reliability and validity, matching that of in-person testing conducted in English (Swaminathan et al, 2021), and that performance did not vary as a function of testing language.…”
Section: Methodssupporting
confidence: 65%
“…General cognitive ability (hereafter cognitive ability) was tested with the Matrix Reasoning Item Bank (MaRs-IB; Chierchia et al, 2019). The MaRs-IB, which has been used successfully by a variety of independent research groups (e.g., Correia et al, 2021; Nussenbaum et al, 2020), is a freely available online measure of abstract (nonverbal) reasoning modeled after Raven’s Advanced Progressive Matrices (Raven, 1965). The test has 80 trials.…”
Section: Methodsmentioning
confidence: 99%
“…This study did not also measure musical ability in any way and relied on self-reported measures of musical sophistication. Although scores on this questionnaire correlate well with tests of musical ability, such as melody or rhythm detection, further research is needed using similar online measures of musical ability such as the Musical Ear Test 23 , 36 . The nature of the method used to study our participants did not allow us to get detailed information about the computer setup they were using, which may have been very important in certain tasks such as that for perceptual precision.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not expect large effects of the day of invitation on participation, taking advantage of small but systematic variations in people's willingness to participate in studies, would be a cost-free and low threshold measure to increase data quantity. Along with other papers published in this journal (e.g.,Anwyl-Irvine et al, 2021;Correia et al, 2021;Grootswagers, 2020;Söderström et al, 2021), the present study thus adds to our knowledge on advancing the quality of online studies.Several studies have examined whether the day of the week affects participation in online surveys. In ad hoc studies, there is some limited evidence that participation is higher in the beginning of the week Zheng (2011).…”
mentioning
confidence: 63%